The public policies of education in recent Brazil: a new look on the education of the municipality of Ruy Barbosa- RN - Freire, Aluizia do Nascimento (Revista Hipótese, 2019)
The purpose of this article is to analyze the public policies responsible for the implementation of educational policies of the Ministry of Education (MEC), the role played by the National Fund for Education Development (FNDE), as well as the Fund for Maintenance and Development of Education Basic and Appreciation of the Education Professional (FUNDEB). Thus, it aims to observe how these policies were implemented in the city of Ruy Barbosa, in the interior of the State of Rio Grande do Norte (RN), and are distributed with the purpose of improving the education of public education in the municipalities.
Keywords: Publics Politics; FNDE; FUNDEB